The associations of circulating common and uncommon polyunsaturated fatty acids and modification effects on dietary quality with all-cause and disease-specific mortality in NHANES 2003–2004 and 2011–2012. (1st January 2021) - Zhang, Yuntao; Guo, Xiaoyu; Gao, Jian; Wei, Chunbo; Zhao, Shengnan; Liu, Zhipeng; Sun, Hu; Wang, Jiemei; Liu, Lin; Li, Ying; Han, Tianshu; Sun, Changhao
Abstract: Background: Associations of dietary or supplementary intake of several unsaturated fatty acids and mortality have been widely studied but the results were still hitherto inconsistent or limited. It is still need to explore the effects of these fatty acids by using the objective biomarkers. Objective: We aimed to investigate the relevancy of several serum n-3 and n-6 fatty acids with all-cause and disease-specific mortality to confirm their health effects and effects on the associations between dietary quality and all-cause mortality. Methods: A total of 4132 people from NHANES 2003–2004 and 2011–2012 and the mortality information was confirmed from the NDI. CPH models adjusted for known risk factors were conducted to explore the associations between circulating n-3 and n-6 fatty acids and all-cause or CVD or cancer mortality under complex sampling. We further evaluated their effects on association between dietary quality and all-cause mortality. Results: A total of 437 deaths occurred during the mean follow-up of 83.34 months, including 157 CVD death and 100 cancer death. Serum LA, ALA, EPA and DHA were associated with all-cause mortality (HR in quintile5: LA:0.584, 95%CI: 0.387–0.882, P trend = 0.011; ALA:0.626, 95%CI: 0.432–0.907, P trend = 0.008; EPA:0.535, 95%CI: 0.375–0.764, P trend = 0.001; DHA:0.669, 95%CI: 0.468–0.955, P trend = 0.031). Additionally, serum EPA and ALA were respectively related to CVD and cancer mortality (Q5 HR: EPA:0.450, 95%CI: 0.23–0.854, P trend = 0.009; ALA:0.387, 95%CI: 0.167–0.900, P trend = 0.022). Serum AA, GLA, DGLA and SDA were not associated with any risk of mortality. The effect on all-cause mortality of the lower AHEI scores can be improved by adherence to a higher serum LA, EPA and DHA (in the lowest AHEI strata, LA in tertile3 compared to tertile1 HR:0.596, 95%CI: 0.366–0.970; EPA:0.660, 95%CI: 0.454–0.959; DHA:0.666, 95%CI; 0.444–1.000). Conclusions: Our results support the recent dietary recommendations to increase the intake of plant-derived and marine-derived n-6 and n-3 to improve the ability of primary and secondary prevention.